2013
DOI: 10.1111/jgs.12268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nurse Practitioner Comanagement on the Care of Geriatric Conditions

Abstract: Background/Objectives The quality of care for geriatric conditions remains poor. The Assessing Care of Vulnerable Elders (ACOVE)-2 model (case finding, delegation of data collection, structured visit notes, physician and patient education, and linkage to community resources) improves the quality of care for geriatric conditions when implemented by primary care physicians (PCPs) or by nurse practitioners (NPs) co-managing care with an academic geriatrician. However, it is unclear whether community-based PCP-NP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 20 publications
(41 reference statements)
0
93
0
Order By: Relevance
“…Four studies evaluated and compared how NP-physician co-management of patient care impact compliance with completing recommended care guidelines (Ganz et al, 2010; Litaker et al, 2003; Ohman-Strickland et al, 2008; Reuben et al, 2013). In patients with hypertension, elevated cholesterol, and/or diabetes, several diagnosis-specific care guidelines are recommended to improve the quality of care delivered by the PCP in an effort to improve patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies evaluated and compared how NP-physician co-management of patient care impact compliance with completing recommended care guidelines (Ganz et al, 2010; Litaker et al, 2003; Ohman-Strickland et al, 2008; Reuben et al, 2013). In patients with hypertension, elevated cholesterol, and/or diabetes, several diagnosis-specific care guidelines are recommended to improve the quality of care delivered by the PCP in an effort to improve patient outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with hypertension, elevated cholesterol, and/or diabetes, several diagnosis-specific care guidelines are recommended to improve the quality of care delivered by the PCP in an effort to improve patient outcomes. For example, Reuben et al (2013) found that 71% of overall recommended guidelines were completed with NP-physician co-management compared to 35% completed by a single physician ( p <.001). This study was rated by the researchers as high quality, with limited bias identified.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a study found that elderly patients reported statistically similar satisfaction levels with care regardless of whether their primary provider was a NP or a physician [37]. Another study found that, in community based practices, geriatric patients receiving PCP-NP co-managed care had better outcomes than those receiving care from a PCP only [38].…”
Section: Discussionmentioning
confidence: 94%
“…It utilizes principles of co-management, in this instance by registered nurses and PCPs, that have been demonstrated to be effective in improving the quality of care and the clinical outcomes of chronic conditions. 7, 26, 27, 28 STRIDE also partners with community-based fall prevention programs that have been found to reduce falls. Moreover, the intervention actively engages patients in their care through motivational interviewing and attention to risk factors that are their initial and subsequent highest priorities.…”
Section: Discussionmentioning
confidence: 99%